Vitamin D and Insulin Resistance in Non-Diabetic Women's Interagency HIV Study Participants - Adeyemi, Oluwatoyin M. (Mary Ann Liebert, Inc., 2013)
We explored the relationship between vitamin D levels and insulin resistance (IR) among 1082 nondiabetic (754 HIV-infected) women enrolled in the Women's Interagency HIV study (WIHS), a large and well-established cohort of HIV infected and uninfected women in the US. Vitamin D levels 20–29 ng/mL were considered insufficient and <20 ng/mL deficient. IR was estimated using the homeostasis model assessment (HOMA) and a clinically significant cut-off ≥2.6 was used for HOMA-IR. In the unadjusted analysis, women who were vitamin D insufficient or deficient were 1.62 (95% CI: 1.01–2.61, p=0.05) and 1.70 (95% CI: 1.11–2.60, p=0.02) times more likely to have HOMA values≥2.6 compared to women with sufficient vitamin D. The association did not remain significant after adjustment for factors associated with IR. Among the 754 HIV-infected women, current PI use (OR 1.61, 95% CI: 1.13–2.28, p=0.008) remained independently associated with HOMA ≥2.6 while vitamin D insufficiency (OR 1.80, 95% CI: 0.99–3.27, p=0.05) was marginally associated with HOMA ≥2.6 after adjustment. Ethnicity, body mass index, smoking status, and hepatitis C status were independently associated with insulin resistance in HIV-infected and uninfected women. We found a marginally significant association between vitamin D insufficiency and insulin resistance among nondiabetic HIV-infected WIHS women.